Danes and Icelanders in Michigan - Nicholson, Howard L. (Book collections on Project MUSE., 2013)
Immigration of Danes and Icelanders to Michigan began in the 1850s and continued well into the twentieth century. Beginning with their origins, this book takes a detailed look at their arrival and settlement in Michigan, answering some key questions: What brought Danes and Icelanders to Michigan? What challenges did they face? How did they adjust and survive here? Where did they settle? What kind of lasting impact have they had on Michigan's economic and cultural landscape? Extensively researched, this book examines the public and private lives of Danish and Icelandic immigrants in Michigan, drawing from both individual and institutional histories. Shedding new light on the livelihood, traditions, religion, social life, civic organizations, and mutual benefit societies, this thorough, insightful book highlights a small but important population within Michigan's borders.